Revision surgery after failure of lateral unicompartmental knee replacement with a mobile-bearing device: a retrospective non -designer case-series - Hariri, Mustafa; Freytag, Jakob; Koch, Kevin-Arno; Mick, Paul; Nees, Timo A.; Knappe, Kevin; Renkawitz, Tobias; Walker, Tilman (Archives of orthopaedic and trauma surgery, 2025)
Introduction: Failure of lateral unicompartmental knee replacement (UKR) with a mobile-bearing (MB) device often occurs due to bearing dislocation. The effectiveness of various treatment options for revision surgery is not clear. Therefore, the purpose of this study was to report on the failure modes in lateral MB-UKR, as well as the results of different revision strategies. Materials and methods: Patients who experienced failure of lateral MB-UKR and required revision surgery at a single-center between 2008 and 2020 were included in this retrospective study. The aim of the study was to report the reasons for failure and to document all treatment strategies employed. Survivorship analysis was conducted using the Kaplan-Meier estimator, with the endpoint defined as ‘re-revision for any reason’. Survival rates among various treatment strategies were compared using the log-rank test. Results: A total of 13 patients were included in the study, with a mean follow-up (FU) period of 94.7 ± 36.4 months. The reasons for failure included bearing dislocation in 69.2%, progression of osteoarthritis (OA) in 23.1%, and periprosthetic joint infection in 7.7%. Treatment options included replacement of the tibial component with a fixed-bearing (FB) device in 23.1% of cases, solitary exchange of the bearing in 53.8%, or conversion to an unconstrained total knee replacement (TKR) in 23.1%. The re-dislocation rate in patients who underwent a bearing exchange as a treatment for bearing dislocation was 100%, with a mean FU period of 8.4 ± 11 months. Therefore, survivorship for the treatment of bearing dislocation differed significantly in these patients compared to those who received an exchange to a FB device (0% vs. 100%, p = 0.014). Conclusions: Addressing the recurring issue of bearing dislocation in lateral MB-UKR demands a more comprehensive approach than merely replacing the bearing. Effective solutions include replacing the tibial component with an FB design or converting to an unconstrained TKR. Level of evidence: Retrospective cohort study, Level IV.